Identifikasi Komponen Volatil Asap Cair Daun Tembakau (Nicotiana tabacum L.) Rajangan - Kuntjahjawati Kuntjahjawati; Purnama Darmadji (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Tobacco smoke contains both a particulat and gaseous phase. Many compounds associated with tobacco smoke are known to cause certain health risks i.e; nicotine, nitrosamine, PAH compound etc. An alternative methode to minimize health risks is to produce liquid smoke. In this study, liquid smoke is produced by pirolysis of tobacco leaf containing 7.08% cellulose, 21.955% hemicellulosa , 9.115 % lignin and nikotin 3.05%. The pirolysis was carried out in a reactor at 400